Peran Penyuluhan Dalam Pemberdayaan Petani Kelapa Sawit Pola Swadaya di Kecamatan Tambusai Utara Kabupaten Rokan Hulu - Andi Joko Pramono; Rosnita '; Arifudin ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purposes of this research are: (1) To identify the role of extension toward independent smallholder farmers of palm oil; (2) To know the empowerment level of the farmers; (3) To analysis the relation between extension’s role on empowerment the farmers. This research was conducted at Bangun Jaya Village at North Tambusai Sub-district of Rokan Hulu. Samples were determined by purposive sampling methods with consideration that the location has active extension activities and has farmers group. 45 independent smallholder farmers of palm oil were taken as respondent. Validity and reliability analysis has been done on the measuring instruments. Data’s analysis to acknowledge the first and second research purpose used Scale Likert’s summated Rating (SLR), whereas multiple linear regression used to acknowledge the third purpose of this research. The Result showed that: (1) The extension role is categorized enough, that are consisted of facilitation, supervision, monitoring and evaluation is categorized enough, while on education, information dissemination, and consultation is categorized have a role; (2) The empowerment level is categorized well, that are consisted of human resources and productive economy is categorized well, while on institutional is well enough; (3) Empowerment of independent small holder farmers affected significantly by the role of extension in education, facilitation and consultation, and monitoring and evaluation, however the role of extension does not significantly affect on dissemination and supervision of the farmers empowerments. Keywords: Role of extension, empowerments, independent smallholder farmers, palm oil